Respuesta :
Answer:
5(x + 4)(x - 2)
Step-by-step explanation:
Start by factoring 5 out of all three terms. We then have
5(x^2 + 2x - 8), or
5(x^2 + 2x - 8), which is in proper quadratic form.
Note that (4)(-2) = 8 and that 4 - 2 = 2, which match the 3rd and 2nd coefficients of x^2 + 2x - 8.
Thus, in completely factored form, we have 5(x + 4)(x - 2)
Answer:
5 (x -2) (x +4)
Step-by-step explanation:
5x^2 + 10x - 40
Factor out a 5
5(x^2 +2x-8)
We can then factor inside the parentheses
What two numbers multiply to -8 and add to 2
-2*4 = -8
-2+4 = 8
5 (x -2) (x +4)